Performance evaluation of supercritical CO2 Brayton cycle with two-stage compression and intercooling - Jiahui Jiang; Yongqiang Yu; Yuanyang Zhao; Guangbin Liu; Qichao Yang; Yunxia Liu; Liansheng Li (Case Studies in Thermal Engineering)
Due to its small structures and high energy efficiency, the Brayton cycle using supercritical carbon dioxide (sCO2) can be implemented in various energy industries. The simulation model for a sCO2 recompression Brayton (RB) system with a two-stage compression and intercooling process (TCIP) is developed. At the design working conditions, there are minimum and optimum split ratios for the sCO2 RB with TCIP cycle. The sCO2 RB with TCIP cycle has a broader range of split ratios compared to the RB cycle. The sCO2 RB with TCIP cycle can achieve a minimum split ratio of 0.315, compared to 0.36 for the sCO2 RB cycle. The maximum efficiency of the sCO2 RB with TCIP cycle is 50.95 %, which surpasses the efficiency of the sCO2 RB cycle by 3.14 %. There exists an optimal value for the first-stage pressure ratio because the maximum efficiency of the sCO2 RB with the TCIP system tends to increase and then decrease with the increase in the first-stage pressure ratio. The pressure ratio of 1.1 for the first-stage compressor, corresponding to an interstage pressure of 8.25 MPa, maximizes the efficiency of the sCO2 RB with the TCIP cycle. The results can be used to further explore the applicability of sCO2 RB with TCIP.